Síntese e caracterização de um catalisador de platina nanoestruturado suportado em sílica mesoporosa de fácil recuperação para reações de hidrogenação em fase líquida - Wizbiki, Marilene (2015)
A new Pt nanosctrure-based catalyst resembling a “core-shell” system was synthesized. This material is composed of magnetite nanoparticles coated by a silica matrix containg Pt(0) nanoparticles decorating its surface. It was tested in hydrogenation reaction of polyaromatic hydrocarbons (PAHs). Anthracene was chosen as standard substrate. The Pt catalyst was used in liquid-phase hydrogenation with H2 as a clean source of H atoms. The method did not require any additional reducing substances environmentally unfriendly, in accordance with Green Chemistry principles. Many reaction parameters such as temperature, H2 pressure and reaction time was varied in order to obtain the best optimized operational conditions. Surprisingly, the magnetic recoverable platinum catalyst was able to convert more than 90% of the substrate into its partial hydrogenated counterparts under ultra-mild conditions (35 oC, PH2 = 1.5 atm, t= 60 minutes). The intrinsic magnetic property of the support allowed the catalyst to be isolated rapidly from liquid samples, using a small Nd magnet (4000 G) placed on the external reactor wall. The liquid phase containing the products were characterized and quantified by GC-MS and UV-VIS Spectrometer. Besides the catalyst study, the magnetic cores, catalytic support and the catalytic Pt phase were characterized using modern techniques that provided a complete physical, chemical and morphological elucidation of the obtained materials. The catalyst Fe3O4@mSiO2-Pt0 was applied in hydrogenation of anthracene, which was the polyaromatic hydrocarbon chosen as substrate, in mild reaction conditions (P = 6 atm; T = 75 C and time = 35 min). The same proved to be efficient in the catalytic reduction can be used for up to two times under these conditions.